Glycemic Control in Patients with Diabetes on Peritoneal Dialysis: From Glucose Sparing Approach to Glucose Monitoring - Aleksandra Kezić; Selena Gajić; Ana Račić Ostojić; Ivana Bekić; Ana Bontić; Jelena Pavlović; Marko Baralić; Ljiljana Popović (Life)
Optimized glycemic management is crucial for controlling atherosclerosis and consequent cardiovascular morbidity in patients with diabetes. Due to the continuous glucose burden from glucose-containing peritoneal dialysis (PD) solutions, PD patients with diabetes experience difficulties in glucose level regulation with glucose hypervariability and worsening dyslipidemia. Even in non-diabetic PD patients, glucose-containing PD solutions aggravate insulin resistance and cause overweight. Additionally, glucose degradation products (GDP) from glucose-based PD solutions provoke oxidative stress and complex inflammatory processes, leading to chronic deleterious and fibrotic peritoneal membrane changes. In this narrative review, we searched the literature using PubMed, MEDLINE, and Google Scholar over the last three decades to summarize the most important facts relevant to the presented issues, aiming to inform both endocrinologists and nephrologists in providing the best currently available care for people with diabetes on PD. We not only focus on adequate tailoring of insulin therapy adapted at the time of PD exchange with hypertonic glucose solution., but also emphasize the use of continuous glucose monitoring (CGM) that allows assessment of mean glucose values and time spent in normal, hypo, and hyperglycemia. However, the routine use of CGM in PD patients is limited due to high cost, and hemoglobin A1c (HbA1c) analysis is still recommended as a basic clinical tool for the assessment of glycemic control. Possible choices of antidiabetic drugs were considered given the narrowed choice due to contraindications for metformin and sulfonylurea. The other important therapeutic approach in PD patients with diabetes is using glucose-sparing PD regimens based on icodextrin and amino acid PD solutions with the addition of just one or two bags of low glucose concentration PD solution daily. This glucose-sparing approach not only reduces the glucose load and improves glycoregulation with correction of the lipid profile but also maintains the viability of the peritoneal membrane by reducing the harmful effects of GDPs.